EFFECT OF PHOSPHORUS AND ZINC FERTILIZATION ON GROWTH AND QUALITY OF CLUSTERBEAN [CYAMOPSIS TETRAGONOLOBA (L.) TAUB.] - MEENA, K.R.; DAHAMA, A.K.; REAGER, M.L. (Annals of Agricultural Research, 2014)
A field experiment was conducted to study the effect of four levels of phosphorus (0, 20, 40 and 60 kg P2O5 ha-1) and five levels of zinc (0, 2.5, 5, 7.5 and 10 kg ha-1). The results showed that application of phosphorus significantly increased plant height, number of branches per plant and dry matter accumulation at harvest, root nodules, and LAI at 45 DAS, chlorophyll content at 30, 45 and 60 DAS and protein and gum content of clusterbean upto 40 kg P2O5 ha-1 over lower doses. Increasing levels of zinc increased the plant height, number of branches per plant, dry matter accumulation, LAI and protein content upto 7.5 kg zinc ha-1 and dry weight of root nodules, gum content and chlorophyll content at 45 and 60 DAS upto 5 kg zinc ha-1, while chlorophyll content at 30 DAS of clusterbean increased upto 2.5 kg zinc ha-1.